Dynamic Effects of Financial Development, Trade Openness and Economic Growth on Energy Consumption: Evidence from South Africa - Rafindadi, Abdulkadir Abdulrashid; Ozturk, Ilhan (International Journal of Energy Economics and Policy, 2017)
This paper investigates whether financial development, trade openness and economic growth add to the energy consumption in South Africa and determine what policy guide could be derived with respect to energy consumption vis-Ã -vis the industrialization process of other African countries for the period of 1970-2011. The unit root properties of the data were examined using the Ng-Perron unit root tests and the traditional structural break unit root tests by Zivot-Andrew was applied. The cointegration properties of the data was observed using the ARDL bounds test approach to cointegration and the Bayer-Hanck combined cointegration test, while the VECM Granger causality approach is applied to examine the causal relationship between the series and this is validated using the innovative accounting approach. Our results show that financial development stimulates energy demand in South Africa; affluence is positively linked with energy consumption, while trade openness also increases energy consumption. We recommend the exploration of several unrestricted energy sources which will sustain the country's leading role as Africa's largest industrial economy, while other rising continents in Africa should note that sustainable energy Granger cause economic growth and thus the secret behind South Africa's leading economic growth prospects. Keywords: Energy consumption; Trade openness; Financial Development; Bayer-Hanck Cointegration; Economic growth JEL Classifications: F4, N7, Q43